Pressões ambientais, esquemas interpretativos e estratégias: um estudo nos atacados e distribuidores mercearis do estado do Paraná - Pereira, Géri Luis Scherwinski (2008)
The main purpose of this study was verifying how the intepretative schemes from mercearis wholesalers and distributers CEO´s of Parana state acted as mediators on strategies used by the companies of this sector, when working under pressuring environment in this segment during the period from 2003 to 2007. It was taking into concern a theory board about the context of pressuring enviroment, interpretative schemes and enterprise strategies. The study rely on a quantitative description analysis once is based among descriptive and quantitative methods to collect data. Initially, a document research was made through a structured questionnaire with questions of simple and multiples choices, using the Likert scale. The research was then sent to 653 companies and 141 samples were returned. The analysis of these information is showing that among the respondent, there is a domination of small and medium companies, considering the Brazilian classification of employes quantity. The data analysis was made through the quantitative method VARIMAX which found a positive result of 52,213% on total variation and the sample found five variables origins, which were classified as: (i) strategy and pressure about differentiation, (ii) strategy and pressure about maintenance, (iii) strategy and pressure about imitation, (iv) strategy and pressure about socio-political, (v) strategy and pressure about costs. The clusters analysis was the objetive to join the organization mercearis considering the reference context with the intention of evaluating similar characteristics of acting, as well as considering the interpretation of enviroment and the preassuring, trying to identify the differences on the strategy level. It was noted four groups in the reference context, which was microregional, by states, state/national and nationals. Referring to the clusters analysis, it became notable the correlation between the groups mentioned and selected in the study, showing homogeneity in the units observed and heterogeneity when compared within the same group as far as a reference context. Also considering the groups, it is important to mention that we noted even the groups have the same values and reference context, there is a variation on emphasis of each one. We can consider that the different strategies are result of the value given by each company on products, services, market, human resources, financials and technologiques. Finally, the research conclusion clearly show the importance of the leaders mental models in the organization mercearis in the interpretations of the referring context, resulting on strategies choices that follow the same pattern with the organization guiding. This conclusion is confirmed when considering the existence of different groups for the enviroment context and in the strategies used by the sector in the period evaluated.